A Study of Digital Media Content Needs for Early Childhood Education on Balikpapan Tourism - Anggis Rizky Wiyaringtyas; Hesti Rosita Dwi Putri; Nursanti Novi Arisa (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to identify the needs for digital media content to introduce Balikpapan tourism to early childhood learners. A qualitative descriptive approach was employed through interviews with teachers and parents at Al Azhar Kindergarten 58 Balikpapan. The findings indicate the necessity for educational media that integrates Balikpapan’s local cultural values, includes parental supervision features, and utilizes child-friendly visual designs to enhance learning motivation while balancing digital engagement with real-world exploration. These insights serve as the foundation for developing culturally grounded digital media for early childhood, which is expected to strengthen cultural identity and provide a more meaningful learning experience.